Helicobacter pylori infection in gastric carcinoma in the Van region of Turkey - , M. Kürşat TÜRKDOĞAN, Süleyman ALICI, Mahmut İLHAN and , Hüsniye DİLEK and , Emel AKMAN and , Hayati AYAKTA and , Metin KARAKÖK (Turkish Journal of Gastroenterology 1, 2019)
-